Modeling of a future scenario of potential sea level rise and consequences to land use in the Cananéia-Iguape Estuarine-Lagoonal Complex (Brazil) - DALMAS, Fabrício Bau; OJEDA ZÚJAR, Jose; FRAILE-JURADO, Pablo; PARANHOS FILHO, Antonio Conceição; OLIVEIRA, Ana Paula Garcia; SAAD, Antonio Roberto; MACEDO, Arlei Benedito (Pesquisas em Geociências, 2020)
The objective of this study was to develop possible future land use scenarios for the Cananéia-Iguape Estuarine-Lagoonal Complex by the analysis of the land use evolution along 24 years (1986-2010), and to predict scenarios for 2025. In order to predict the scenario of the land use and occupation classes of 2025 a simulation was carried out by means of the Markov chain methods and calibration of the simulation model in the IDRISI Andes program. In the phase prior to this step it was utilized TM sensor scenes (Landsat 5) and supervised classification techniques to simulating the land use and occupation map of 2010 from land use and occupation maps from 1986 and 1999. Then the land use and occupation map of 2010 was utilized inside de Markov chain to simulate the map of 2025. By applying the techniques proposed by Titus and Narayanan, Pfeffer, Ramhstorf and the Intergovernmental Panel on Climate Change (IPCC) model, the vulnerability of the study area was calculated taking into consideration a potential sea level rise in 2025, 2050 and 2100. In the last step of the applied method, land use and occupation classes were assessed, which will possibly be affected by a highest tide event in 2025. It was observed that 80.92% the area flooded during highest tide events in 1999 was composed of dense arboreal vegetation and it is concluded that this expansion of the dense arboreal vegetation area will also occur towards the coastal zone in 2025. We suggest that the local factor for sea level rise in the study area has a strong geological component, so that, instead of a mere sea level rise, an opposite movement is taking place, which is the subsidence of the plain due to modern tectonism.